In vitro characterization of sonothrombolysis and echocontrast agents to treat ischemic stroke - Himanshu Shekhar (Nature Portfolio, 2019)
Abstract The development of adjuvant techniques to improve thrombolytic efficacy is important for advancing ischemic stroke therapy. We characterized octafluoropropane and recombinant tissue plasminogen activator (rt-PA)-loaded echogenic liposomes (OFP t-ELIP) using differential interference and fluorescence microscopy, attenuation spectroscopy, and electrozone sensing. The loading of rt-PA in OFP t-ELIP was assessed using spectrophotometry. Further, it was tested whether the agent shields rt-PA against degradation by plasminogen activator inhibitor-1 (PAI-1). An in vitro system was used to assess whether ultrasound (US) combined with either Definity or OFP t-ELIP enhances rt-PA thrombolysis. Human whole blood clots were mounted in a flow system and visualized using an inverted microscope. The perfusate consisted of either (1) plasma alone, (2) rt-PA, (3) OFP t-ELIP, (4) rt-PA and US, (5) OFP t-ELIP and US, (6) Definity and US, or (7) rt-PA, Definity, and US (n = 16 clots per group). An intermittent US insonation scheme was employed (220 kHz frequency, and 0.44 MPa peak-to-peak pressures) for 30 min. Microscopic imaging revealed that OFP t-ELIP included a variety of structures such as liposomes (with and without gas) and lipid-shelled microbubbles. OFP t-ELIP preserved up to 76% of rt-PA activity in the presence of PAI-1, whereas only 24% activity was preserved for unencapsulated rt-PA. The use of US with rt-PA and Definity enhanced lytic efficacy (p < 0.05) relative to rt-PA alone. US combined with OFP t-ELIP enhanced lysis over OFP t-ELIP alone (p < 0.01). These results demonstrate that ultrasound combined with Definity or OFP t-ELIP can enhance the lytic activity relative to rt-PA or OFP t-ELIP alone, respectively.